2011
DOI: 10.1080/00074918.2011.556055
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment and growth in East Asia: lessons for Indonesia

Abstract: Foreign direct investment (FDI) has been important in the growth and global integration of developing economies. Both Northeast and Southeast Asia, especially the latter, have been part of this development, with increasing inflows of FDI and greater foreign participation in local economies. However, Indonesia has been an outlier within the region. Inflows of FDI have been lower to Indonesia than to other countries, especially in manufacturing, and they have been lower than could be expected from Indonesia's si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 63 publications
3
38
0
3
Order By: Relevance
“…R&D spending as a share of GDP was even lower in 2005 than it was in the 1990s (only 0.05% of GDP); meanwhile US majority-owned manufacturing affiliates operating in Indonesia were spending only 0.06% of employee compensation, or $80 per employee, on R&D in 2004 (Lipsey and Sjöholm 2011). 20 The comparable figures for US firms operating in China were 14.9% of employee compensation and $1,492 per employee.…”
Section: The History Of Cement In Indonesiamentioning
confidence: 83%
See 3 more Smart Citations
“…R&D spending as a share of GDP was even lower in 2005 than it was in the 1990s (only 0.05% of GDP); meanwhile US majority-owned manufacturing affiliates operating in Indonesia were spending only 0.06% of employee compensation, or $80 per employee, on R&D in 2004 (Lipsey and Sjöholm 2011). 20 The comparable figures for US firms operating in China were 14.9% of employee compensation and $1,492 per employee.…”
Section: The History Of Cement In Indonesiamentioning
confidence: 83%
“…China's actual trade share is nearly 45% higher than expected, while Indonesia's is only 9% higher than expected. 6 Lipsey and Sjöholm (2011) argue that the stock of inward foreign direct investment (FDI) in Indonesia is much lower (only 59%) than might be expected for a country with its characteristics, while China's stock of inward FDI is roughly what can be expected. 7 Price controls, non-tariff barriers (NTBs) and import licensing and quotas have virtually disappeared from China (Branstetter and Lardy 2008), while NTBs and price controls have become more common in Indonesia (Basri and Hill 2008).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Lipsey and Sjöholm argued that American firms chose to locate their labour-intensive production in Indonesia only when alternatives were not available elsewhere. They concluded that environmental conditions such as infrastructure, education, and corruption become all-important as soon as investors can pick a host country at will (Lipsey and Sjöholm 2011). It was the responsibility of Indonesian policymakers to provide better conditions.…”
Section: Figure 3 Approved Foreign Direct Investment Inmentioning
confidence: 98%